If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x+3=-12x
We simplify the equation to the form, which is simple to understand
6x+3=-12x
We move all terms containing x to the left and all other terms to the right.
+6x+12x=-3
We simplify left and right side of the equation.
+18x=-3
We divide both sides of the equation by 18 to get x.
x=-0.166666666667
| s^2+18sz+80z^2=0 | | x^2+0x+9= | | -3z+.5=20 | | 3(q-2)+2=5q-72q | | 56x^7+21x^4+9X^3= | | 0=9y^2-64 | | m*7=-18 | | (x-5)*(x-7)=0 | | 10-3(2x+4)=4x+28 | | 2w-8+w^2=0 | | 81x^7+36x^8+63x= | | 0=2x^2-x+2 | | 9x^2+4x+21=0 | | 9=m-0.006 | | 9-6x=45x-4 | | x^2-x+16=0 | | -9x^2+4x+21=0 | | 13x^2-131x-250=0 | | (2+xi)(3-2i)=12+5i | | 2x^2+9x-216=0 | | -x^4+3x^2+x=256 | | -2x+5/2=17 | | x/2+5x/6+x/4=380 | | 0.05x+0.20*300=0.10(x+300) | | 0.05x+0.20*100=0.10(x+100) | | (3x+4)(6x-1)= | | 2w+1(w)-45=0 | | 0.05x+0.20*100mL=0.10(x+100mL) | | (6x+4)(3x-1)= | | 40.77=y/5+2.4y+y/10 | | 12x+15-36-8x=0 | | 2(x^2+7x-141)=0 |